Fulminant Fournier's gangrene in a patient with gastric cancer treated with ramucirumab and paclitaxel - Zoran Rakusic; Ana Misir Krpan; Ivica Sjekavica (SAGE Publishing, 2020)
Fournier's gangrene (FG) is an uncommon form of necrotizing fasciitis, localized on the external genital organs, perianal region, and abdominal wall, accompanied by thrombosis of the feeding arteries, leading to gangrene of the skin and subcutaneous tissue, with manifestations of rapid clinical progression and multiple organ failure. Ramucirumab is a recombinant human immunoglobulin G1 monoclonal antibody that binds to the extracellular binding domain of vascular endothelial growth factor receptor-2 (VEGFR-2) and prevents the binding of all VEGFR ligands. The literature describes bevacizumab, aflibercept, and regorafenib associated with FG in patients with colorectal cancer. According to our knowledge this is the first report of FG possibly related to ramucirumab in a patient with gastric cancer. If not recognized in time, it can lead to fatal complications.